FULL-TIME EDUCATION IN BRAZIL: CHALLENGES AND POTENTIAL OF EDUCATIONAL LAW FOR THE IMPLEMENTATION OF EQUALITY AND EQUITY IN PUBLIC SCHOOLS - Gigoski, Iarana de Castro; Pacheco, Luci Mary Duso (Seven Editora, 2025)
This article aims to analyze how public education policies aimed at promoting equality and equity interact with the foundations of Educational Law, focusing on the reality of full-time public schools in Brazil. The research adopts a qualitative approach, based on a critical bibliographic review and hermeneutic interpretation of official documents, legislation, and relevant academic works. The methodology allowed for the identification and analysis of the main normative and theoretical frameworks that support the proposal for comprehensive education in the country, considering both its pedagogical foundations and its normative dimension. The results indicate that, although extending the school day constitutes an important advance, it is not sufficient, in itself, to guarantee a comprehensive education guided by equity. The effectiveness of comprehensive education policies depends on factors such as adequate funding, ongoing teacher training, coordination with the local community, and a commitment to pedagogical practices that recognize the diversity of individuals. Educational Law proves fundamental as a foundation for the development of structural policies capable of promoting social justice through education. It is concluded that strengthening full-time public schools requires actions that integrate the principles of Educational Law with critical and emancipatory curricular proposals, promoting student empowerment, inclusion, and social transformation. Consolidating this policy as a promoter of equity requires intentionality, social participation, and a political commitment to democratizing access to knowledge and citizenship.DOI: https://doi.org/10.56238/sevened2025.030-073